2019
DOI: 10.1176/appi.ps.201800450
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Mobile Crisis Services on Emergency Department Use Among Youths With Behavioral Health Service Needs

Abstract: Youths are using emergency departments (EDs) for behavioral health services in record numbers, even though EDs are suboptimal settings for service delivery. In this article, the authors evaluated a mobile crisis service intervention implemented in Connecticut with the aim of examining whether the intervention was associated with reduced behavioral health ED use among those in need of services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 20 publications
0
21
0
Order By: Relevance
“…Up to 50% of children and youth admitted to psychiatric inpatient units experience boarding (waiting for an extended time) in EDs or medical inpatient units, sometimes for days (McEnany et al, 2020 ) Reducing ED utilization 16. There are promising initiatives to reduce ED utilization through mobile and community crisis services, START programs, and learning communities focused on EDs and their community partners (Fendrich et al, 2019 ; Kalb et al, 2016 ) a Some data has been simplified for presentation in the Fact Sheet format. Additional data is available in the body of the article and the cited sources …”
Section: The Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…Up to 50% of children and youth admitted to psychiatric inpatient units experience boarding (waiting for an extended time) in EDs or medical inpatient units, sometimes for days (McEnany et al, 2020 ) Reducing ED utilization 16. There are promising initiatives to reduce ED utilization through mobile and community crisis services, START programs, and learning communities focused on EDs and their community partners (Fendrich et al, 2019 ; Kalb et al, 2016 ) a Some data has been simplified for presentation in the Fact Sheet format. Additional data is available in the body of the article and the cited sources …”
Section: The Approachmentioning
confidence: 99%
“…There are, however, at least three areas of work that have shown recent promise. An analysis of Connecticut Medicaid data found a significant reduction in the odds of a repeat ED visit and total number of ED visits among children and youth who received mobile crisis services in comparison to those who were not mobile crisis recipients (Fendrich et al, 2019 ). At a large urban hospital in Brooklyn, New York, the establishment of an outpatient Urgent Evaluation Service appeared effective in reducing unnecessary pediatric ED mental health visits among predominantly Medicaid insured Latinx, Chinese, and South Asian immigrant populations (Alvarado et al, 2020 ).…”
Section: Categories Of Informationmentioning
confidence: 99%
“…The virtual and 24/7 access provided by helplines may be especially critical during the natural disasters and public health emergencies like the COVID-19 pandemic, when the formal behavioral healthcare system may be less accessible and anxiety levels and social isolation may be heightened (Costa et al, 2020 ). Helplines may also offer an important alternative to using emergency services, along with other resources such as mobile crisis response (Fendrich et al, 2019 ) or referrals to other mental health services.…”
Section: Discussionmentioning
confidence: 99%
“…9 Fendrich et al found that youths who received MCO services had decreased odds of having a behavioral health ED visit. 19 How MCO services may differentially affect adults vs youths is unknown. Our MCO program was focused on adult patients who had more limited family support, and that focus may have led to the increase in reported return visits.…”
Section: Discussionmentioning
confidence: 99%